2009
DOI: 10.1007/s00432-009-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options in dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans (DFSP) is a rare malignant dermal neoplasm characterized by slow infiltrative growth, little metastatic potential but a high tendency to recur locally after surgical excision. DFSP is associated with a high cure rate. The optimal therapy is complete surgical resection. The recurrence potential of DFSP is directly related to the extent of resection. The need for wide excision margins has been amply documented. Wide local excision is a frequently used practice. Mohs micrographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
220
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(251 citation statements)
references
References 127 publications
9
220
1
12
Order By: Relevance
“…However, the response from patients remains poor and locoregional recurrence has been observed during follow-up (10)(11)(12). The natural history of DFSP is low-grade malignancy, with a 26-60% local recurrence rate attributed to incomplete excision due to poor circumscription and irregular boundaries (13). The lesion typically infiltrates well beyond its grossly visible margin into the surround tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the response from patients remains poor and locoregional recurrence has been observed during follow-up (10)(11)(12). The natural history of DFSP is low-grade malignancy, with a 26-60% local recurrence rate attributed to incomplete excision due to poor circumscription and irregular boundaries (13). The lesion typically infiltrates well beyond its grossly visible margin into the surround tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion typically infiltrates well beyond its grossly visible margin into the surround tissue. Certain studies have advocated the use of Mohs micrographic surgery with incremental excision until normal tissue is obtained, as documented by repeat frozen sections (13). Several studies have demonstrated a significant correlation between a wide excision and a low recurrence rate (9,13).…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is classified as a rare tumor, however, it may be considered as the most common stromal tumor of cutaneous origin (7). Numerous epidemiological studies in the USA have reported a mean annual incidence rate between 0.8 and 4.5 cases per million individuals (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, Criscione and Weinstock (12) studied 9 population-based cancer registries with a total of 2,885 DFSP cases and reported a higher incidence in females. It has also been found that DFSP has a higher incidence rate among individuals aged between 20 and 50 years (13); however, several studies have reported more than 160 pediatric cases of acquired DFSP and more than 35 congenital cases (7,(14)(15)(16)(17)(18)(19). In addition, it has been demonstrated that giant cell fibroblastoma is the juvenile form of dermatofibroblastoma arising in childhood (20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, dermatofibrosarcoma protuberans is characterized by a 17;22 translocation involving the COL1A1 and PDGFB genes, which results in the overproduction of fusion COL1A1-PDGF-BB ligand and consequent hyperactivation of PDGFRB, rendering these tumors responsive to targeted therapy with tyrosine kinase inhibitors such as imatinib mesylate. 47,48 The aim of the following is to highlight indications for molecular testing in the management of soft-tissue tumors and the advantages of capitalizing on these methods when facing tumors of a confusing nature or challenging differential diagnosis. Certain case illustrations are included to serve as useful paradigms.…”
Section: Indications For Molecular Testing In Sarcomas; Capitalizing mentioning
confidence: 99%